Decarbonization scenarios for the iron and steel industry in context of a sectoral carbon budget: Germany as a case study. (20th December 2022) - Harpprecht, Carina; Naegler, Tobias; Steubing, Bernhard; Tukker, Arnold; Simon, Sonja
Abstract: CO2 emissions from global steel production may jeopardize climate goals of 1.5 °C unless current steel production practices will be rapidly decarbonized. At present, primary iron and steel production is still heavily dependent on fossil fuels, primarily coke. This study aims to determine which decarbonization pathways can achieve the strongest emission reductions of the iron and steel industry in Germany by 2050. Moreover, we estimate whether the German iron and steel industry will be able to stay within its sectoral carbon budgets for a 1.5 °C or 1.75 °C target. We developed three decarbonization scenarios for German steel production: an electrification, coal-exit, and a carbon capture and storage (CCS) scenario. They describe a phase-out of coal-fired production plants and an introduction of electricity-based, low-carbon iron production technologies, i.e. hydrogen-based direct reduction and electrowinning of iron ore. The scenarios consider the age and lifetimes of existing coal-based furnaces, the maturity of emerging technologies, and increasing recycling shares. Based on specific energy requirements and reaction-related emissions per technology, we calculated future CO2 emissions of future steel production in Germany. We found that under the decarbonization scenarios, annual CO2 emissions decrease by up to 83% in 2050 relative to 2020. The reductions of cumulative emissions by 2050 range from 24% (360 Mt CO2 ) under the electrification scenario up to the maximum of 46% (677 Mt CO2 ) under the CCS scenario compared to a reference scenario. This clearly demonstrates that the technology pathway matters. Nevertheless, the German steel sector will exceed its sectoral CO2 budget for a 1.5 °C warming scenario between 2023 and 2037. Thus, drastic measures are required very soon to sufficiently limit future CO2 emissions from German steel production, such as, a rapid decarbonization of the electricity mix, the construction of a hydrogen and CCS infrastructure, or early shutdowns of current coal-based furnaces. Graphical abstract: Image 1 Highlights: Scenarios for iron and steel production in Germany until 2050 Adopting new technologies: hydrogen-based direct reduction and electrowinning Comparison of CO2 emissions with sectoral carbon budgets for the steel industry Carbon budget for climate goal of 1.5 °C likely to be exceeded between 2023 and 2037 Carbon capture scenario achieves lowest CO2 emissions but has higher energy demand